2018
DOI: 10.1021/acs.est.7b06508
|View full text |Cite
|
Sign up to set email alerts
|

Porous Electrospun Fibers Embedding TiO2 for Adsorption and Photocatalytic Degradation of Water Pollutants

Abstract: Using a bipolymer system consisting of polyvinylpyrrolidone (PVP) and poly(vinylidene fluoride) (PVDF), P25-TiO was immobilized into thin film mats of porous electrospun fibers. Pores were introduced by dissolving sacrificial PVP to increase surface area and enhance access to TiO. The highest photocatalytic activity was achieved using a PVDF:PVP weight ratio of 2:1. Methylene blue (MB) was used to visualize contaminant removal, assess the sorption capacity (5.93 ± 0.23 mg/g) and demonstrate stable removal kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
137
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(154 citation statements)
references
References 56 publications
2
137
1
Order By: Relevance
“…Another point of difference is the color change; the color of RhB changed from red to transparent. However, Cossich et al's research did not mention about the color change, and the color of MB changed from blue to gray with all MB completely degraded in Lee et al's research . One further point of difference is 80% of RhB in our research was degraded quickly, with the reminding 20% degrading slowly under visible light.…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…Another point of difference is the color change; the color of RhB changed from red to transparent. However, Cossich et al's research did not mention about the color change, and the color of MB changed from blue to gray with all MB completely degraded in Lee et al's research . One further point of difference is 80% of RhB in our research was degraded quickly, with the reminding 20% degrading slowly under visible light.…”
Section: Resultscontrasting
confidence: 59%
“…The peak area of methylene blue at 662 nm gradually decreased until disappearing after irradiation by UV light for 120 min. Lee et al used PVP/TiO 2 /PVDF with PVP to PVDF of 1:2 to degrade methylene blue under UV irradiation. The result showed that the color of MB changed from light blue to purple after 240 min immersion of nanofibers in 3 mg L −1 MB solution under darkness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is needed to develop a feasible, professional, and effective method to separate oil and water. Photocatalytic water treatment achieves oxidative degradation of many organic pollutants using light irradiation without chemical addition . Titanium dioxide (TiO 2 ) is considered to be an ideal photocatalysis that has been commonly studied due to its high activity, strong chemical stability, nontoxicity, low production cost, photocatalytic properties, and self‐cleaning capability .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, with a range of doping and heterojunctions, TiO 2 can be used to degrade various organic pollutants under UV–visible (λ > 360 nm) or visible light (λ > 420 nm) as well. However, the main pollutants that are targets for degradation are dyes and phenol‐like organic pollutants (Lee et al, ; Likodimos, ; Xing et al, ; Zada et al, ; Zalfani et al, ; Zhang, Li, Li, Li, & Yang, ). Studies on the degradation of emerging contaminants (ECs) under UV–visible or visible light are few.…”
Section: Introductionmentioning
confidence: 99%